Đề vậy mới đúng nè bạn :))?
$\text{Rút gọn các biểu thức sau:}$
`a, A = 100^2 - 99^2+ 98^2 - 97^2 + ... + 2^2 - 1^2`
`=(100-99)(100+99)+(98-97)(98+97)+...+(2-1)(2+1)`
`=(1+100).100:2`
`=5050`
`b, B = 3(2^2 + 1) (2^4 + 1) ... (2^{64} + 1) + 1^2`
`=(2^2-1)(2^2+1)(2^4+1)(2^8+1)....(2^{64}+1)+1`
`=(2^{16}-1)(2^{16}+1)(2^{32}+1)....(2^{64}+1)+1`
`=2^{128}-1+1=2^{128}`
` c, C = (a + b + c)^2 + (a + b - c)^2 - 2(a + b)^2`
`=a^2+b^2+c^2+2ab+2ac+2bc+a^2+b^2+c^2+2ab-2ac-2bc-2(a^2+2ab+b^2)`
`=2c^2+0+0+0`
`=2c^2`